Genome-wide association study of 23,500 individuals identifies 7 loci associated with brain ventricular volume - Dina Vojinovic (Nature Portfolio, 2018)
An increase in the volume of the brain lateral ventricles is a sign of normal aging, but can also be associated with neurological and psychiatric disorders. Here, Vojinovic et al. identify seven genetic loci in a GWA study for ventricular volume in 23,500 individuals and find correlation with thalamus volume.